Pursuing sustainability through multi-stakeholder collaboration: A description of the governance, actions, and perceived impacts of the roundtables for sustainable beef. (September 2019) - Buckley, Kristy J.; Newton, Peter; Gibbs, Holly K.; McConnel, Ian; Ehrmann, John
Highlights: Roundtables for sustainable beef (RSBs) address cattle sector sustainability. We trace the governance, actions, and impacts of national and global RSBs. Multi-stakeholder RSBs are pursuing continuous improvement, not certification. RSBs have developed principles and criteria, definitions, and working groups. RSBs impacts may include coordination roles, geographic expansion, and verification. Abstract: Roundtables for sustainable beef have evolved in national contexts as well as at the global level as a multi-stakeholder process to address sustainability concerns in the cattle sector. However, due to their relatively recent inception, the literature on the beef roundtables is extremely limited and very little scholarly work has traced their process or impact. We used semi-structured interviews with key informants to examine the governance, actions, and potential impacts of the roundtables for sustainable beef, and identified opportunities and challenges for achieving greater sustainability impact. We found that the beef roundtables are in different stages of development and implementation and that they have diverse approaches based on their geographic contexts. However, they have universally adopted a model of sector-wide continuous improvement, in contrast to roundtables for other commodities, which have in many cases adopted formal certification programs. Activities by the roundtables for sustainable beef have variously included working towards definitions of sustainable beef; setting sustainability principles and criteria; and creating working groups to address specific aspects of sustainability (e.g., verification, deforestation). Our interviews identified opportunities to expand the roundtables' roles, activities, and sustainability impacts. This study provides a benchmark of the roundtables' efforts to date, and generates hypotheses and ideas for how they could evolve in the future.